Web bearing capacity of unlipped cold-formed ferritic stainless steel channels with perforated web subject to end-two-flange (ETF) loading. (1st December 2017) - Yousefi, Amir M.; Lim, James B.P.; Clifton, G. Charles
Highlights: Web bearing tests of unlipped cold-formed ferritic stainless steel channels. Non-linear quasi-static finite element models are developed. A parametric study considering different sizes is performed. Web bearing capacity design equations are proposed for incorporating into design. Abstract: In this paper, laboratory and numerical evaluations on the web bearing capacity of unlipped cold-formed ferritic stainless steel channels are described. The channels considered have circular perforations in the web and are loaded under the end-two-flange (ETF) load case. A total of 387 results comprising 27 laboratory and 360 numerical results are presented. A nonlinear quasi-static finite element (FE) model was developed for the numerical investigation. An extensive parametric study is described to determine web bearing capacity reduction factors for different sizes of circular web perforations and cross-section dimensions; the circular web perforations are either centred or offset to the load and reaction plates. It is noted that no cold-formed stainless steel standard provides capacity reduction factors for any end-two-flange load case. The capacity reduction factor equations are first compared to reduction factors previously recommended for lipped cold-formed stainless steel channels. It is found that these existing equations are unreliable and unconservative for unlipped channels by as much as 11%. The laboratory investigation shows that, for the case of plain unlipped channels (i.e. without web perforations), the ASCE Specification (SEI/ASCE 8-02) is conservative by as much as 14%. From both laboratory and finite element results, web bearing capacity design equations are proposed for both sections, with and without perforations in the web.